Affect and subjectivity of child welfare policy workers in Chile - Javiera Garcia-Meneses; Giazú Enciso-Domínguez (Íconos)
In recent decades, affect theory has gained interest in the study of work and subjectivity. Due to its focus on pre-conscious and sensory factors, the study of affect has enabled understanding the production of subjectivity overcoming rational models of subjectivity that (re)produce an ideal of the sovereign neoliberal subject. This article seeks to affectively analyze the labor subjectivity of workers in the Chilean child protection program. We carried out a digital ethnography with six workers of the Servicio Nacional de Menores [National Service for Minors]. One of the interviews conducted was analyzed considering that the particular experience of this interviewee describes a co-constitutive relationship with other subjects of the program. We analyzed the data using the technique of textual-affective and carnal-word analysis. Our findings indicate that these workers' subjectivities are constituted by/in the assemblage of their bodies with other bodies – human and non-human – that are part of the childhood program. In the assemblages with human bodies, the workers are endowed with agency, enabling new ways of inhabiting their daily workspaces. Thus, by studying the production of subjectivity from an affect lens, it is possible to reclaim and recover the voices of the workers in the child protection program by understanding them as a central and fundamental element in the gears from which this social program emerges.